A framework for the selection of projects at the county level in Croatia - Krpan, Ljudevit (Array, 2021)
This paper presents a framework for regional self-government units for the selection of projects expected to have a substantial positive effect on the socio-economic characteristics of the broader community. The previous experience of administrative bodies at all levels (national, regional and local) indicates that the decision to implement certain project and programme activities was primarily based on political decision-making principles and a voluntarist approach. With the adoption of the acquis communautaire, the Republic of Croatia has provided legal prerequisites for the selection and implementation of projects based on established criteria, with the criterion of impact on the quality of life and development usually being the dominant one. Therefore, the goal of this paper is to describe the frame-work and procedure of the evaluation and selection of public projects at the regional level, which can easily be applied to decision-making at both the national and local levels.